EDUCATIONAL STRATEGIES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores educational strategies for children with autism spectrum disorder (ASD). It examines opportunities to develop children’s academic and social skills through individualized approaches and innovative methods in the educational process.